MALAYAN MUSLIMS AS A REFLECTION OF MALAYNESS IN ANTHONY BURGESS’S ‘TIME FOR A TIGER’ - Sahiddan, Nurhanis (Jurnal Pengajian Melayu (JOMAS), 2020)
In one of the most overlooked English literary text on the Malay World, namely Anthony Burgess’ novel Time for a Tiger (1956), the depictions of Islamic practices through the Malay characters show their hypocrisy and that they are wayward Muslims (Zawiah Yahya, 2003). This paper then seeks to explore the role of Islam as a paradigm of Malayness in literature portrayed through characters understood to be Malay. The objectives of this study are met by undertaking a close reading of the text as a methodology to explore how the Malay characters understand and practise Islam, and to discover whether they conform to the Islamic beliefs as understood by non-Muslims; here, to Burgess’ understandings of Malayan Islam. The conceptual framework is based on the paradigm of Malayness in literature as an everydaydefined social reality consisting of six elements – the Malay language, Islam, the Malay rulers, adat/culture, ethnicity and identity (Ida Baizura Bahar, 2010) as opposed to it as an authority-defined social reality comprising only of Islam, the Malay language and the Malay rulers (Shamsul A. B., 2001). The findings demonstrate that Burgess could have made an implicit criticism of Malayan Muslims by mocking the reality of the Malays through his observations during his stay in Malaya and that the paradigm of Malayness in literature is not an authority-defined but an everyday-defined social reality. Findings from this study therefore can contribute to the on-going discourse on Islam and Malayness in literature as well as English Literature on the Malay World. Keyword: Malayness, Islam, Muslims, English literature on the Malay world